STRATEGI BUMDES DALAM UPAYA PENDIRIAN SENTRA UMK BERBASIS KOPERASI KERAKYATAN YANG BERBADAN HUKUM UNTUK KESEJAHTERAAN MASYARAKAT - Setiawan Adi Pratama (ECONOMOS, 2022)
Optimizing the function of BUMDes in Kedung Sumber village to become the main mover in efforts to improve the economy in Kedung Sumber village, knowing that BUMDes is trying to start a role with one of the programs for establishing UMK centers which aims to empower business actors in Kedung Sumber village in a center with management in the form of a cooperative with a legal entity. The analytical method used in the strategy of establishing a UMK center in Kedung Sumber village is using qualitative descriptive analysis. Data from interviews, observations, and questionnaires that have been filled out are then processed using SWOT analysis which aims to determine the factors that influence the strategy for establishing a UMK center in Kedung Sumber village. The journey of the center forward is the role of BUMDes as an institution that plays a role in efforts to improve the economy of rural communities, and also has opportunities that also affect the village of Kedung Sumber which has the potential as an independent village in improving the community's economy by empowering business actors through the establishment of UMK centers. A good strategy to use for the establishment of UMK centers is a hold and maintain strategy, namely market penetration to expand marketing networks, attract visitor arrivals, and develop product innovations. Based on the SWOT analysis, the strategy for establishing a UMK center is able to help the welfare of business actors and improve the economy of the Kedung Sumber village community.